The Role of Competence, Work Environment, and Emotional Intelligence to Influence Employee Performance in an Indonesian Regional Civil Service Agency - Wangi, Putri Ayu Tirta; Pogo, Tajuddin; Prayitno, Sahri (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This study aims to determine the effect of competence, work environment, and emotional intelligence on employee performance. Methodology/approach – The research design is causal quantitative with SEM PLS data analysis method using the SmartPLS 3.0 application with the population being employees of one of regional civil service agencies in Indonesia and a sample of 184 employees using purposive sampling in determining sample. Findings – From this study, positive and significant effect given by competence, work environment, and emotional intelligence on employee performance. Several indicators that have the greatest influence on the variables studied include accuracy, teamwork, and emotional control so that these indicators can be reviewed for improvements to increase performance. Novelty/value – This research has contributed to the development of existing research construct models. This study further strengthens the influence of the variables of competence, work environment, and emotional intelligence on employee performance and answers the previous research gap. there are indications of other variables that can affect employee performance and this is an opportunity that can be taken for further research.